PELATIHAN DAN PENDAMPINGAN STRATEGI PEMASARAN DAN PROMOSI DESTINASI WISATA DESA ADAT SUWAT DALAM IMPLEMENTASI PARIWISATA BERKELANJUTAN - Mahayasa, I Gede Aryana; Dewi, Ida Ayu Sasmita; Wulandari, Ni Luh Adisti Abiyoga; Wijaya, Putu Yudy; Sudiana, I Wayan; Suartina, I Wayan (BESIRU : Jurnal Pengabdian Masyarakat, 2024)
This community service was carried out in the traditional village of Suwat, Gianyar Regency to help answer the problems faced by the managers and administrators of tourist destinations in Suwat village. The purpose of this community service activity is to provide an understanding of marketing and promotion strategies that can be carried out to increase tourist visits to Suwat village. The training method is used to assist in formulating marketing and promotion strategies for tourist destinations. From this activity, the results obtained are that Suwat Waterfall as a tourist destination in Suwat village has the potential to become a reliable and well-known tourist destination by implementing several marketing and promotion strategies, such as conducting digital promotions, increasing promotional aggressiveness, and establishing cooperation with related parties.